Minutes
001-0003-001 PRIVATE & CONFIDENTIAL MINUTES OF MEETING OF THE HOUSING SUB-COMMITTEE OF THE STANDING JOINT COMMITTEE OF INDUSTRIAL WOMEN'S ORGANISATIONS HELD AT TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W. I. ON WEDNESDAY, 11th NOVEMBER, 1936, AT 5. p.m. 1. PRESENT: Alderman Rose Davies (in the Chair), Mrs. Adamson, Mrs. Barton, Mrs. Pugh, Mrs. Short and Miss Sutherland (Secretary). 2. APOLOGIES FOR ABSENCE: Apologies for absence were received from Mrs. James and Mrs. Leighton. 3. PERIOD OF ENQUIRY: After full discussion it was agreed that the enquiry should be postponed until after the County and District Council Elections and the National Conference of Labour Women which it was proposed to hold in April, 1937. 4. SCOPE OF ENQUIRY: It was agreed that the enquiry should cover the following questions:- 1. Defects in existing municipal housing schemes: to include planning, equipment, labour saving appliances, etc. 2. The Houses working women want: accommodation, planning, equipment, cooking facilities, gardens, etc. 3. Flats. 4. Amenities on new housing estates: halls, nursery schools, schools, etc. 5. Houses for old people. 6. Houses for single workers. 7. Rural Houses. It was agreed that a statement and questionnaire on these points should be drafted; and if possible, pictures and plans of various types of houses and housing estates estates obtained for circulation with the questionnaire. This concluded the business. 292/946/1/3